2019
DOI: 10.1590/1983-40632019v4955718
|View full text |Cite
|
Sign up to set email alerts
|

Maize cropping systems and response of common bean in succession subjected to nitrogen fertilization1

Abstract: The common bean succession to intercropped crops in the no-tillage system is beneficial, especially in the search for sustainability. In addition to the straw production, the intercropping can supply nitrogen (N) to the common bean grown in succession, reducing the use of mineral fertilizer, which is pollutant and has a high cost. The present study aimed to evaluate the response to N fertilization of common bean in succession to maize cropping systems, as well as the viability of these systems in the no-tillag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 20 publications
1
10
1
Order By: Relevance
“…These plants accumulate more N in the aerial part than stylo, forage peanut and calopo (Mendonça et al, 2017), making this nutrient available to the common bean cultivated in succession. N is the most exported nutrient by common bean, being a constituent of proteins and molecules such as chlorophyll, besides being related to the increase in photosynthetic rate, leaf growth, development of vegetative and reproductive organs and biomass production (Taiz et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…These plants accumulate more N in the aerial part than stylo, forage peanut and calopo (Mendonça et al, 2017), making this nutrient available to the common bean cultivated in succession. N is the most exported nutrient by common bean, being a constituent of proteins and molecules such as chlorophyll, besides being related to the increase in photosynthetic rate, leaf growth, development of vegetative and reproductive organs and biomass production (Taiz et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…In general, it was observed that the cropping successions with maize and U. ruziziensis did not interfere in the agronomic performance and seed yield of common bean cultivated in succession. Evaluating the effect of common bean in succession to maize, maize + U. ruziziensis and maize + Crotalaria, Souza et al (2019) observed that the common bean yields were similar in succession after maize in sole crop and maize + U. ruziziensis and superior in succession to maize + Crotalaria. This same result was observed in the present study, in which the seed yields of common bean were similar between the grass cropping successions.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike the results obtained by Souza et al . (2019), the common bean successions evaluated in the present study were conducted after cropping successions only of grasses in sole crop and intercropped. As grasses have a higher C/N ratio than legume crops, such as Crotalaria, the degradation of straw from these plants is slower and promotes temporary immobilization of soil N, even if the straw is not incorporated (Liu et al ., 2017; Williams et al ., 2018).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations